al-Af’âl al- Ṡulâṡiyah al-Mazîdah wa Ma’ânîhâ fî Kitâb Safînah al-Najâh (Dirâsah Taḥlîliyyah Ṣarfiyyah) - Aang Saeful Milah; Mila Santi (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
Kitab Safînah al-Najâh, together with other classical Arabic books can explain how Indonesian Muslims live their lives in regard with religious aspects. The book since long has been widely thought in most of traditional Islamic education institutions (pesantren) in Indonesia for it is considered relatively concise but comprehensive, covering basic laws of daily religious activities. The conciseness of the book, however, may lead to problems of misinterpretation. The biggest assumption of this regard relies on the use of complex broken verbs, called in Arabic as Fi'il Ṡulâṡi Mazîd, which refer to different meanings. This article aims at analysing the meanings that may come from the use of Fi'il Ṡulâṡi Mazîd in the book Safinah al-Naja from the perspective of morpho-semantic. It is found 55 patterns of Fi'il Ṡulâṡi Mazîd. From this amounts, there are 26 verbs with additional one character (Mazîd bi harfin), 25 verbs with additional two characters, and 4 verbs with additional three characters. Some of these verbs come with various meanings